Pathological sports heart - Schantarovich, V.; Kallaur, E.; Marinich, V. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
Considering the necessity of timely heart's pathological transformation diagnostics of athletes engaged in cyclic sports here are presented results (got during kayaks and canoe oarsmen activity) of research on studying standard electrocardiogram, echocardiography, biochemical markers changes of athletes' myocardium injury with stress-car-diomyopathy signs occurring during the above mentioned athlete's activity. It's apparent that vegetative and metabolic frustration of kayak and canoe athletes with stress-cardiomyopathy signs is accompanied with decrease in physical working capacity. The data obtained makes it possible to broaden the researches used in sports cardiology.